2009
DOI: 10.1111/j.1600-0501.2009.01769.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of repeated screw tightening on bacterial leakage along the implant–abutment interface

Abstract: These results suggest that bacterial leakage between implants and abutments occurs even under unloaded conditions and at a higher intensity when the abutment screw is tightened and loosened repeatedly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 15 publications
2
45
1
7
Order By: Relevance
“…Accumulation of bacteria at this interface 11,12 can be associated with peri-implant mucositis, which is defined clinically as erythema and edema of the soft tissue with bleeding on probing as an important feature.…”
mentioning
confidence: 99%
“…Accumulation of bacteria at this interface 11,12 can be associated with peri-implant mucositis, which is defined clinically as erythema and edema of the soft tissue with bleeding on probing as an important feature.…”
mentioning
confidence: 99%
“…Precaution involving the concentration of bacterial suspensions is already a reality; 4,5,14 but confirmation of bacterial viability was made only in two studies 5,14 . The chosen post-inoculation control test was immersion of the implants up to the I-A interface coating for 30 s. The overflow control by immersion was used in a previous study and showed good results 9 . Currently, in vitro tests for microleakage with corpuscular bacteria showed no flow at the I-A interface, even in hexagonal joints, contradicting what was previously thought 9,14 .…”
Section: Discussionmentioning
confidence: 99%
“…The chosen post-inoculation control test was immersion of the implants up to the I-A interface coating for 30 s. The overflow control by immersion was used in a previous study and showed good results 9 . Currently, in vitro tests for microleakage with corpuscular bacteria showed no flow at the I-A interface, even in hexagonal joints, contradicting what was previously thought 9,14 . Even though these findings may be different in situations of mechanical load, inner joints are more stable and could be more beneficial, but few studies compared this situation 3,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Callan Steinebrunner et al, 2005;Nascimento et al, 2008;Nascimento et al, 2009;Aloise et al, 2010;Cosyn et al, 2011). A maioria dos estudos nesta área têm utilizado métodos tradicionais, como a cultura microbiana, no entanto, estima-se que grande parte das espécies de microrganismos presentes na cavidade oral não são cultiváveis pelos métodos convencionais (Arank et al, 1969), como espécies fastidiosas e microrganismos anaeróbios estritos.…”
Section: Colonização Microbiana Associada Aos Implantes Dentáriosunclassified